2008
DOI: 10.1057/rlp.2008.10
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of vacation ownership amenities with hotel and resort hotel amenities

Abstract: This study evaluated resort amenities of the timeshare and vacation ownership resorts in North and South Carolina and compared the amenities with the amenities of hotels throughout the United States (US), resort hotels in the US and resort hotels in the South Atlantic region of the US The results of this study assist timeshare and vacation ownership resort management to compare their amenity offerings to hotels, provide resort operators and developers a closer look at amenities of existing vacation ownership r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Quality service was also identified by Stringam (2008), Brey and Choi (2010), Anastassova (2011) and Van Vuuren and Slabbert (2011), while Kim et al (2000), Lucas and Tanford (2010), Brey and Choi (2010) and Konu et al (2011) identified factors similar to activity. Accessibility was identified by Meng, Tepanon and Uysal (2006), Stringam (2008), andVan Vuuren and. However, similar attributes were identified as factors on their own and not in combination with others, as is the case in this research.…”
Section: How Do Tourists Rate Resort Amenities and Attributes?mentioning
confidence: 97%
“…Quality service was also identified by Stringam (2008), Brey and Choi (2010), Anastassova (2011) and Van Vuuren and Slabbert (2011), while Kim et al (2000), Lucas and Tanford (2010), Brey and Choi (2010) and Konu et al (2011) identified factors similar to activity. Accessibility was identified by Meng, Tepanon and Uysal (2006), Stringam (2008), andVan Vuuren and. However, similar attributes were identified as factors on their own and not in combination with others, as is the case in this research.…”
Section: How Do Tourists Rate Resort Amenities and Attributes?mentioning
confidence: 97%
“…Lawton, Weaver, & Faulkner [32] concluded that the onsite and nearby amenities, children's activities, and entertainment options associated with timeshare resorts in Australia added to the satisfaction level of timeshare owners. In a study on timeshare resorts in the United States' Carolinas, the fourth largest geographic U.S. market in terms of concentration of timeshare resorts, Stringam [2] determined that amenities related to timeshare resorts were comparable with amenities offered in resort lodging properties. According to Stringam [2], the following were listed as the most common amenities associated with timeshare resorts: swimming pools, exercise rooms, children's activities, and tennis courts for onsite amenities; WIFI internet access, DVD players, and CD players for in-unit amenities.…”
Section: Joj Sciencesmentioning
confidence: 99%
“…Existing academic literature on vacation ownership reveals two primary areas of focus each with their related attributes: the purchase process [37][38][39], and the usage/experience process [1,2,[31][32][33]37]. The dimensions identified in academic literature were examined and validated by industry professionals to ensure that no items had been overlooked.…”
Section: Applying the Framework To The Vacation Ownership Productmentioning
confidence: 99%
See 1 more Smart Citation